Vibro-tactile Feedback for Real-world Awareness in Immersive Virtual Environments - Valkov, Dimitar; Linsen, Lars (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2019)
In immersive virtual environments (IVE), users' visual and auditory perception is replaced by computer-generated stimuli. Thus, knowing the positions of real objects is crucial for physical safety. While some solutions exist, e. g., using virtual replicas or visible cues indicating the interaction space boundaries, these are limiting the IVE design or depend on the hardware setup. Moreover, most solutions cannot handle lost tracking, erroneous tracker calibration, or moving obstacles. However, these are common scenarios especially for the increasingly popular home virtual reality settings. In this paper, we present a stand-alone hardware device designed to alert IVE users for potential collisions with real-world objects. It uses distance sensors mounted on a head-mounted display (HMD) and vibro-tactile actuators inserted into the HMD's face cushion. We implemented different types of sensor-actuator mappings with the goal to find a mapping function that is minimally obtrusive in normal use, but efficiently alerting in risk situations.